Copy fights : the future of intellectual property in the information age - Thierer, Adam; Crews, Wayne; McCullagh, Declan (CATO Institute, 2002)
The modern information revolution has created a whole new set of policy issues concerning property rights. Including contributions from figures from high-profile companies, this book analyses the issues involved.